Cover Feature: Towards Size‐Controlled Deposition of Palladium Nanoparticles from Polyoxometalate Precursors: An Electrochemical Scanning Tunneling Microscopy Study (ChemElectroChem 7/2021). Issue 7 (17th March 2021) - Bock, Nicolas; De Clercq, Astrid; Seidl, Lukas; Kratky, Tim; Ma, Tian; Günther, Sebastian; Kortz, Ulrich; Heiz, Ueli; Esch, Friedrich
Abstract : The Cover Feature illustrates a novel in situ electrochemical approach to deposit small size‐controlled palladium(0) clusters from palladium‐oxo‐metalate precursors. Their formation by reductive surface polarization of a Au(111) support is explored by electrochemical scanning tunneling microscopy (EC‐STM). More information can be found in the Article by N. Bock et al .